Analysing Critical Thinking and Microlearning Based English Speaking Learning Materials for Students with Mild Intellectual Disabilities - Siti Drivoka Sulistyaningrum; Rosevinda Nabila Putri; Atika Herawati (Journal of English Language Studies, 2023)
The advancement of the microlearning method has been prevalent and facilitates the pedagogical approach to develop students' critical thinking in 21st-century learning. However, research into English learning materials for speaking, particularly critical thinking and microlearning-based English learning materials for speaking for mildly intellectually disabled students, is limited. Thus, this study reports the existence of microlearning-based learning materials scripts for English-speaking 8th graders for mildly intellectually disabled students, infused with critical thinking skills by employing content analysis. This study uses framework of microlearning from Allela (2021) and critical thinking taxonomy from Anderson & Krathwohl. (2001). Â The following are the procedures for analysing critical thinking and microlearning-based English speaking learning materials for students with mild intellectual disabilities: 1) choosing microlearning and critical thinking descriptors; 2) analysing current book content using microlearning and critical thinking skills descriptors; 3) categorizing descriptors that have not covered in existing learning materials. Â The findings revealed that the material is not fully infused with critical thinking and microlearning descriptors. The advancement of the microlearning method has been prevalent and facilitates the pedagogical approach to develop students' critical thinking in 21st-century learning. However, research into English learning materials for speaking, particularly critical thinking and microlearning-based English learning materials for speaking for mild intellectually disabled students is limited. Thus, this study reports the existing of microlearning-based learning materials scripts for English-speaking 8th graders for mild intellectually disabled students, infused with critical thinking skills by employing content analysis. The findings revealed that the material is not fully infused with critical thinking and microlearning descriptors.